EDUKASI PENTINGNYA MENCUCI TANGAN YANG BAIK DAN BENAR DI SDIT ROBBANI BANJARBARU - Hilda Irianty; Ridha Hayati (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The results of preliminary observations was SDIT Robbani that students there have washed part is actually visible hand of sediakannya of wash their hands in front of the their classes but the knowledge they wash their hands not based on six step washing the hands that is good and right. The purpose of this activity to give education the importance of washing good hands and right. This method of activity consists of lectures, question reply, and simulation of the game with the population number and sample of 10 students.As for the activity, it's divided into the first three stages of permission., second planning and third execution. The result of this activity after being given an education on good and correct hand washing students can learn the techniques of good and correct hand washing in six steps as well as provide discipline in hand washing after active. The conclusion of this activity other students can understand the wash hand that is good and right with the six steps Keywords: Education,washing your hands,Students